EVALUATION OF THE EFFECTS OF MENOPAUSE ON SALIVA - Dr.Rutu Jani, Dr Shashwat K. Jani, Dr Rajita S. Jani, Dr Akash Patel, Dr. Dhaval Dave (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
Background & Objective: Menopause leads to physiological changes that take place due to decreased production of estrogen by ovary in women. The study was carried out to know the effect of menopause on saliva by evaluating the unstimulated salivary flow rate, viscosity, pH and stimulate salivary flow rate and buffering capacity in menopausal females. Method: The study was conducted on 50 healthy post-menopausal women (group I) and 30 pre-menopausal women (control- group II), 20 males of similar age group as group I (control- group III) respectively, who attended outpatient department of Oral Medicine and Radiology of Ahmedabad Dental College and Hospital. Data were collected through a questionnaire and oral examination. Samples of the stimulated and unstimulated saliva were taken. A standard size paraffin wax was chewed by participants for stimulated saliva collection. Flowrate was measured by observing saliva at orifices of the minor glands after some time. Viscosity was measure by visual examination. pH was measured using strips. Buffering capacity was measured using buffer test strips. Result and Interpretation: A notable decrease in the unstimulated salivary pH and salivary flow rate, and viscosity as well as stimulated salivary flow-rate and buffering capacity was found in menopausal females compared to the control group. Keywords: Post menopause, Salivary flow rate, Salivary pH, Oral changes